Safety profile of drugs used in non-cystic fibrosis bronchiectasis: a narrative review - Henil Upadhyay; Stefano Aliberti; Andrew Husband; James D. Chalmers; Katy Hester; Anthony De Soyza (SAGE Publishing, 2024)
Non-cystic fibrosis bronchiectasis is a long-term lung disease characterised by abnormal dilatation of the bronchi, with patients experiencing chronic productive cough and recurrent exacerbations. Currently, there are no licensed drugs for use in bronchiectasis while clinical trials have been conducted to either test new drugs or repurpose existing ones. These drugs target the underlying pathophysiology of bronchiectasis which is known to include infection, inflammation, mucus hypersecretion and retention. Most of the drugs used in daily clinical practice for bronchiectasis are off-label with no randomised trials exploring their safety. This review aims at exploring the safety profile of drugs frequently used in clinical practice to manage bronchiectasis, including antibiotics (e.g. macrolides, aminoglycosides, polymyxins, fluoroquinolones, aztreonam), mucoactive therapy (e.g. hypertonic saline, mannitol, DNase and carbocisteine), anti-inflammatory therapy (inhaled corticosteroids) and drugs currently in development for use in bronchiectasis (e.g. brensocatib, benralizumab and itepekimab).